The Fall of Apartheid - Harvey, R. author. aut Link
XV, 257 p.
Keywords: The Fall of Apartheid tells the extraordinary story of how apartheid came into being, secured its ascendancy over the richest and most developed society in Sub-Saharan Africa, and then collapsed. For the first time it reveals the full story of the secret meetings between Africans and Afrikaners in Britain, in which South Africa's current president, Thabo Mbeki, had a direct line to President Botha. Robert Harvey's fascinating narrative helps to illuminate not just the South African problems but also more general issues of conflict- and problem-solving.